Influence of the size of beet root pulp particles on the mode of de-cationization before enzymatic treatment - V. V. Kondratenko; T. Y. Kondratenko; M. A. Tsareva; A. Y. Davydova; N. M. Alabina (Новые технологии, 2018)
The article presents the results of studies on the effect of the size of dry non-granulated beet pulp particles on the process of preliminary decationization. Disubstituted sodium salt of ethylenediaminetetraacetic acid was used as a model complexone in fractional concentrations from a fiducial value of 2.87 g / dm3. The global extremes of the dynamics of the specific electrical conductivity of the system “beet pulp - complexone solution” have been selected as a primary response, as corresponding to the moment of complexone saturation with cations. It’s been established that decatonization of a coarse fraction (≥ 5 mm) requires processing of the pulp with an aqueous solution of complexone with a concentration of 3.49 g / dm3 for ~ 43 minutes, whereas for the fine fraction (